2008
DOI: 10.1161/circep.108.805366
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Esophageal Temperature-Monitoring to Prevent Esophageal Injury During Atrial Fibrillation Ablation

Abstract: A number of complications have been associated with ablation of atrial fibrillation (AF), including arterial thrombo-embolism, pulmonary vein stenosis, phrenic nerve injury, and pericardial tamponade. [1][2][3][4] Esophageal injury, manifested as esophageal perforation or left atrial-esophageal fistula, has been reported after catheter or surgical ablation of AF using radiofrequency (RF) current 5-8 and catheter ablation using high-intensity focused ultrasound (HIFU). 9 Left atrial-esophageal fistula usually i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…A strong relationship between an esophageal temperature rise and pain has been shown by prior study . Use of a proton pump inhibitor might facilitate ulcer healing and prevent the progression from esophageal injury to an atrioesophageal fistula . In contrast, PNI was observed in 7.9% of the patients during the period when 25 to 30 W were applied to the posterior LA, suggesting that the periesophageal vagal nervous system was much more fragile than the esophagus itself to thermal injury.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A strong relationship between an esophageal temperature rise and pain has been shown by prior study . Use of a proton pump inhibitor might facilitate ulcer healing and prevent the progression from esophageal injury to an atrioesophageal fistula . In contrast, PNI was observed in 7.9% of the patients during the period when 25 to 30 W were applied to the posterior LA, suggesting that the periesophageal vagal nervous system was much more fragile than the esophagus itself to thermal injury.…”
Section: Discussionmentioning
confidence: 75%
“…22 Use of a proton pump inhibitor might facilitate ulcer healing and prevent the progression from esophageal injury to an atrioesophageal fistula. 23,24 In contrast, PNI was observed in 7.9% of the patients during the period when 25 to 30 W were applied to the posterior LA, suggesting that the periesophageal vagal nervous system was much more fragile than the esophagus itself to thermal injury. This complication was not observed after a reduction of power only at specific small areas of the posterior LA where the ablation line transversed the esophagus (Figure 2, yellow points).…”
Section: How To Avoid Periesophageal Vagal Nerve Injurymentioning
confidence: 94%
“…Although left atrial-esophageal fistulae are rare (occurring after <0.1-0.25% of AF ablation procedures) [386,420,506,549], injury to the esophagus is common following AF ablation. In several clinical studies, endoscopy performed 1-3 days after AF ablation using RF energy, HIFU, laser balloon, or cryothermia identified an asymptomatic esophageal ulcer (directly behind the LA) in 4-60% (generally 15-20%) of patients [282,428,432,[580][581][582][583][584][585][586][587][588]. The asymptomatic esophageal ulcers were usually healed on repeat endoscopy at 2-3 weeks following treatment with a proton pump inhibitor and a cytoprotective agent such as sucralfate [583,586].…”
Section: Esophageal Injurymentioning
confidence: 99%
“…They mentioned that a possible mechanism of this result might be an "antenna effect" of the metallic tip of the catheter; that is, direct thermal injury from the temperature probe, whereas this remains controversial [12,13]. We set the upper limit of the esophageal temperature at 40°C during the procedure as a safety margin because it has been reported that setting it at less than 40-41°C was associated with a lower complication rate of esophageal injury [5,7,14]; however, there is no clear cutoff value for the temperature setting to avoid esophageal thermal injury [8,15]. As a result, this case achieved a successful AF ablation without any esophageal complications using the Esophastar â .…”
Section: Discussionmentioning
confidence: 99%